MODERN VIEWS ON ETHIOPOLOGICAL FACTORS OF THE DEVELOPMENT OF TEMPOROMANDIBULAR JOINT DISORDERS (LITERATURE REVIEW) - V.F. Makeiev; M.Y. Oliynyk (Ukrainian Medical Stomatological Academy, 2018)
In the analysis of literature devoted to the temporomandibular joint, attention is concerned with differentiation of etiological factors and variants of the mechanism of development of TMD's which were proposed by various authors. These disorders are due to peculiarities of the structure and function of the TMJ. Occlusion is the first and perhaps the most controversial etiological factor in the occurrence of TMD. The price was also important reason for temporomandibular disorders. Nowadays, most researchers include occlusion to the factors associated with the development of TMD, which plays possible role both in the tendency and in preserving TMD. Angle and others of their studies determined the effect of pathological dentition on the development of temporomandibular joints . The authors found that in patients with TMD, the difference between the height of central occlusion and the height of physiological rest was higher than in patients without TMD. Summarizing the results of the study, the authors have established a close relationship between pathological erosion of teeth and the appearance of temporomandibular dislocation. Discussions about the effect of occlusion on TMD have been influenced and limited by therapeutic measures in the occurrence of TMD, but modern researchers work to isolate the multifactorial etiology of temporomandibular disorder and reduce the role of occlusion as the main etiological factor in the onset of TMD. • Ockeson, one of the main etiological factors of temporomandibular disorder, considers psychoemotional factor and stress susceptibility as the main dominance of the muscular component of functional disorders of the masticatory apparatus in combination with myofascial pain. The less important element of occlusion (about 20% of etiological factors) is associated with occurrence of occlusive dysfunctions. Probert et al. having conducted a large-scale study that included 20,673 patients who were victims of road accidents, it has been shown that the incidence of TMD after injury from the seat belt was very low and injury as an independent etiologic factor can not be a trigger factor for TMD. Endotracheal anesthesia is also suggested as a risk factor for the development of TMD in a number of clinical cases and systemic studies. Any association between endotracheal intubation and the development of short-term symptoms of TMD's is likely to occur in patients with such a history of dysfunctional disorders. The physician should be aware of the TMD's etiology, because it allows determining the purpose of the examination and planning of the treatment, as well as to confirm the results of treatment and rehabilitation of the patient.